Side Wage Model of State University Lecturers : (Case Study at Mulawarman University) - Maulana, Indra; Roy, Juliansyah; Widayati, Nurfiza; Awaluddin, Muhammad (Eastasouth Institute, 2025)
This study aims to determine the effect of the working period of civil servant lecturers and education on work wages in side jobs (jobs outside the duties as civil servants) both directly, and through work productivity. The sample of 100 respondents was selected purvosively from the population of PTN lecturers at Mulawarman University who have a minimum education of S2 and group IIIc, by using regression analysis (Structural Model), the results showed that: (1) The working period of civil servants and formal education each had a positive and significant effect on the work productivity of lecturers. The implication is that the competence of lecturers is largely determined by educational factors and work experience. (2) However, only formal education has a significant effect on side job wages, while work experience and work productivity have no significant effect. Indicate that there is no other way to improve the additional employment income of lecturers, except by improving competence through further education.